Late bacille Calmette–Guérin infection with a large focal urinary bladder ulceration as a complication of bladder cancer treatment - Ströck, Viveka; Dotevall, Leif; Sandberg, Torsten; Gustafsson, Christina Kåbjörn; Holmäng, Sten (BJU international, 2011)
Study Type – Therapy (case series)  Level of Evidence 4 What's known on the subject? and What does the study add? Intravesical BCG treatment has been used worldwide for many decades but there are only a few published reports on persisting BCG infection of the urinary bladder. This is the first report on large tuberculosis‐like ulcers of the urinary bladder after intravesical BCG treatment. The finding results in a recommendation to take urine cultures for mycobacteriae in patients with unclear inflammatory lesions in the bladder after instillation of BCG. OBJECTIVE • To report a late bacille Calmette–Guérin (BCG) complication previously not described in the literature. PATIENTS AND METHODS • We reviewed our database with 858 patients treated with BCG from 1986 to 2008 and identified 13 male patients (1.8% of all male patients) who had a large tuberculous‐like bladder ulcer. RESULTS • All patients had high‐grade tumours and seven had tumours invading lamina propria before BCG treatment. A solitary ulceration or inflammatory lesion, 10–50 mm in diameter, was seen at routine follow‐up cystoscopy 2–34 months (median 8 months) after the first instillation. Significantly more patients had been treated with BCG‐RIVM than with BCG‐Tice (10/320 vs. three of 454, P < 0.01). BCG was cultured from urine 3–34 months (median 14 months) after the last instillation. • So far, eight patients have been successfully treated with rifampicin and isoniazid. Nine patients are still tumour‐free 15–66 months (median 44 months) after the last transurethral resection before BCG treatment. • Another three patients had one to two non‐invasive recurrences. One patient had an invasive recurrence and underwent cystectomy. The present study is limited by biases associated with its retrospective design. CONCLUSIONS • This is the first report on persisting BCG infections with large inflammatory lesions in the bladder. Treatment is effective and the oncological outcome is good. • Mycobacterial cultures of the urine should be performed in BCG‐patients with unclear inflammatory lesions in the bladder since a delayed diagnosis of a persistent BCG infection could result in a permanently reduced bladder capacity. • Large studies are warranted to study differences in efficacy and side‐effects between different BCG strains.